Glucose Intolerance and Cancer Risk: A Community-Based Prospective Cohort Study in Shanghai, China - Ke, Juzhong; Lin, Tao; Liu, Xiaolin; Wu, Kang; Ruan, Xiaonan; Ding, Yibo; Liu, Wenbin; Qiu, Hua; Tan, Xiaojie; Wang, Xiaonan; Chen, Xi; Li, Zhitao; et al. (Frontiers in Oncology, 2021)
Background Cancer becomes the leading cause of premature death in China. We aimed to determine the current major risk factors of cancer for targeted prophylaxis. Methods A cluster sampling method was applied to enroll 10,657 community-based adults aged 15-95 years in Shanghai, China in 2013. A structured questionnaire and physical examination were applied in baseline survey. Prediabetes was diagnosed using 75-g oral glucose tolerance test. After excluding 1433 subjects including 224 diagnosed with cancer before and 1 year after baseline survey, the remaining 9,224 subjects were followed-up to December 31, 2019. Results A total of 397 new cancer cases were diagnosed. The cancer incidence was 9.04, 8.37, and 5.41/1,000 person-years in diabetes patients, those with prediabetes, and healthy participants, respectively (p<0.001). The multivariate Cox regression analysis indicated that age, prediabetes, diabetes, and C-reactive protein were associated with an increased risk of cancer in those <65 years, with a hazard ratio (95% confidence interval) of 1.05 (1.03-1.07), 1.51 (1.08-2.12), 1.42 (1.02-1.97), and 1.02 (1.01-1.04), respectively Glucose intolerance (prediabetes and diabetes) were associated with increased risks of stomach cancer, colorectal cancer, and kidney cancer in those <65 years. Anti-diabetic medications reduced the risk of cancer caused by diabetes. The multivariate Cox analysis showed that age, <9 years of education, and current smoking were associated with increased risks of cancer in those ≥65 years independently. Conclusions Glucose intolerance is the prominent cancer risk factor in adults <65 years. Lifestyle intervention and medications to treat glucose intolerance help in cancer prophylaxis in this population.